Sense-Making, Meaningfulness, and Instrumental Music Education - Silverman, Marissa (Frontiers in Psychology, 2020)
The purpose of this paper is to re-examine the nature of “meaning” and “meaningfulness” in the context of instrumental music education. By doing so, I propose to expand the ways in which instrumental music educators conceive their mission and the ways in which we may instill meaning in people’s lives. Traditionally, pursuits of philosophical deliberation have claimed that meaningfulness comes from either personal happiness (e.g., Jeremy Bentham and John Stuart Mill) or an impersonal sense of duty (e.g., St. Augustine, St. Thomas Aquinas, and Immanuel Kant). However, philosopher Susan Wolf (2010) criticizes these positions in favor of a broader perspective, one that arises from understanding that there is a third sort of value, namely “meaningfulness.” Rightly understanding meaningfulness may help us engage more fully with a greater sense and understanding of the full potentials of eudaimonia: a life of significance and value for oneself and one’s community. Therefore, this paper links meaningfulness to a 4-E (embodied, embedded, enacted, and extended) account of “sense-making” in/for instrumental music education. In doing so, I discuss the aims of public-school music education; aims that engage teachers and students in meaningfulness—a meaningfulness that is ethical, embodied, enacted, and extended—in, with, and through musics and, more directly, “instrumental” music making.